3D printing with silk: considerations and applications. (3rd March 2020) - DeBari, Megan K.; Keyser, Mia N.; Bai, Michelle A.; Abbott, Rosalyn D.
ABSTRACT: Silk is a natural polymer sourced mainly from spiders and silkworms. Due to its biocompatibility, biodegradability, and mechanical properties, it has been heavily investigated for biomedical applications. It can be processed into a number of formats, such as scaffolds, films, and nanoparticles. Common methods of production create constructs with limited complexity. 3D printing allows silk to be printed into more intricate designs, increasing its potential applications. Extrusion and inkjet printing are the primary ways silk has been 3D printed, though other methods are beginning to be investigated. Silk has been integrated into bioink with other polymers, both natural and synthetic. The addition of silk is primarily done to offer more desirable viscosity characteristics and mechanical properties for printing. Silk-based bioinks have been used to fabricate medical devices and tissues. This article discusses recent research and printing parameters important for 3D printing with silk.